Effect of eucation level and religion on attitude to stem cells in Malaysia - Latifah Amin,; Hasrizul Hashim,; Maznah Ibrahim,; Anisah Che Ngah,; Nik Marzuki Sidik, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The issue of using stem cells derived from human embryos and adult tissues to treat diseases has been divisively debated mainly due to ethical concerns. The objective of this article was to assess and compare the attitude level of the Malaysian public in the Klang Valley region towards human adult stem cells (hASCs) and human embryonic stem cells (hESCs). Results of the survey on 509 adult respondents revealed that the Malaysian public expressed higher support for hASCs, perceived the application as having lower moral concern and more acceptable by their religion as compared to hESCs. Univariate analysis following Multivariate Analysis of Variance (MANOVA) confirmed that there were significant differences for perceived benefits and religious acceptance of hASCs across education level. Respondents who hold tertiary education level tended to perceive both hESCs and hASCs as more beneficial and believed the applications as more acceptable from their religious point of view. Their opinion of hASCs differed significantly compared to the respondents who hold pre-university education. Respondents from all religions perceived both hESCs and hASCs as having moderate benefits and risks. Significant differences were only detected for perceived moral concerns and encouragement of hESCs across religion. The Christians expressed greater moral concern of both hESCs and hASCs compared to other religions but post hoc test only detected significant difference in their opinion on hESCs from the Buddhists. The Buddhists were found to be more supportive towards both hESCs and hASCs but their support level for hESCs only differed significantly from the Muslims.